Microscopic Colitis with Macroscopic Endoscopic Findings - Atif Saleem; Parag A. Brahmbhatt; Sarah Khan; Mark Young; Gene D. LeSage (Case Reports in Medicine)
Microscopic Colitis (MC) is characterized by chronic watery diarrhea, grossly normal appearing colonic mucosa during conventional white light endoscopy, and biopsy showing microscopic inflammation. We report a case of collagenous colitis with gross endoscopic findings.